Factors associated with the presence of triatomines in rural areas of south Argentine Chaco - Crocco, Liliana Beatriz (2019)
Introduction: The domestic and peridomestic presence of Triatoma infestans depends on several factors, such as human behavior, vector behavior, ecology, and the environment. Methods: This work was conducted in 139 domiciliary units, where triatomines were captured and risk factors in domiciles and peridomicilies were recorded. Household dwellers were interviewed to obtain information about practices regarding this disease and entomological indicators were calculated. Results: Infestation indices were 59.7% for house compounds, 4.3% for domestic areas and 58.3% for the peridomestic areas. Intradomicile infestation was significantly associated with housing characteristics. The presence of chicken coops in peridomicilies was associated with an increased risk of infestation. Of the respondents, 80% did not recognize the importance of the peridomiciliary structures for triatomine control and had infested peridomicilies. Conclusions: The results show the importance of peridomiciles as refuge sites for Triatominae bugs; however, household dwellers do not perceive peridomiciles as areas that favor the presence of vectors. Actions for raising awareness about factors that favor the presence of triatomines are needed to improve the conditions of peridomiciliary environments.